2009
DOI: 10.1021/jm900892x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of a Full-Agonist Orvinol for PET-Imaging of Opioid Receptors: [11C]PEO

Abstract: Antagonist radiotracers have shown only a low sensitivity for detecting competition from high-efficacy agonists at opioid receptors (ORs) in vivo. We report that [(11)C]PEO binds with high affinity to mu and kappa-opioid receptors, is a full agonist, and concentrates in brain regions of rats with a high density of the mu-OR after intravenous injection. Blocking studies with mu and kappa-OR selective compounds demonstrated that the binding of [(11)C]PEO is saturable and selective to the mu-OR in rat brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…Assuming that DAMGO achieved a high level of occupancy, one can conclude that binding to DOR and/or KOR is a nonnegligible contributor to the specific binding in regions such as the striatum, consistent with the literature (3)(4)(5). This reduces the effective specificity of 18 F-FE-PEO to changes in the MOR system, which is the OR subtype of most interest in addiction and pain processing (1,9). Conversion of V T obtained from blood-based kinetic analysis to DVR21 in an effort to increase specificity for MOR is compromised by the spatial heterogeneity of the other OR subtypes and perhaps nonspecific binding; otherwise, normalization with V T in a MOR-devoid area could be a solution.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Assuming that DAMGO achieved a high level of occupancy, one can conclude that binding to DOR and/or KOR is a nonnegligible contributor to the specific binding in regions such as the striatum, consistent with the literature (3)(4)(5). This reduces the effective specificity of 18 F-FE-PEO to changes in the MOR system, which is the OR subtype of most interest in addiction and pain processing (1,9). Conversion of V T obtained from blood-based kinetic analysis to DVR21 in an effort to increase specificity for MOR is compromised by the spatial heterogeneity of the other OR subtypes and perhaps nonspecific binding; otherwise, normalization with V T in a MOR-devoid area could be a solution.…”
Section: Discussionsupporting
confidence: 78%
“…A promising lead for the development of an 18 F-labeled agonist OR ligand was published by Marton et al (9). Their orvinol-type full OR agonist (PEO) showed a central nervous system distribution in accordance with OR receptor expression in the rat brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from our previous investigations [ 6 , 7 , 8 ] have shown that 3- O -trityl-6- O -desmethyl-phenylethyl orvinol (TDPEO, 1 ) is a suitable precursor for the synthesis of [6- O -methyl- 11 C]PEO, an orvinol μ- and κ-agonist radioligand. To benefit from the practical advantages from the longer physical half-life of 18 F, an 18 F-labeled PEO-derivative is attractive.…”
Section: Introductionmentioning
confidence: 99%